Comparative analysis of autoantibodies against alpha-fodrin in serum, tear fluid, and saliva from patients with Sjogren's syndrome - (:unkn) unknown (J RHEUMATOL PUBL CO, 2006)
Objective. To evaluate levels of IgA and IgG antibodies against a-fodrin in serum. tear fluid. and saliva and compare them with anti-Ro and anti-La antibody levels in the same samples of patients with Sjogren's syndrome (SS). Methods. Samples from 25 patients with SS (17 primary and 8 secondary), 8 patients with systemic lupus erythematosus (SLE), and 7 patients with rheumatoid arthritis (RA) as well as 20 healthy blood donor controls were collected. Antibodies were measured using ELISA. Results. Although 40% of patients with primary SS had IgG anti-alpha-fodrin in their sera. it was also found in 36% and 32% of samples of their tear fluid and saliva. respectively. IgA alpha-fodrin antibodies were detected in 32% of SS sera. 20% of tear fluid samples. and 32% of saliva samples. Although the level of IgG anti-alpha-fodrin was significantly greater in serum, tear fluid, and saliva of SS patients compared to controls (p < 0.001), a significant difference was observed only in serum and saliva. While anti-Ro was detected in 48%. 56%, and 24% of serum, tear fluid. and saliva samples, respectively, anti-La was found in 40%. 44%, and 28%. Significant association was observed between serum IgG antibodies against a-fodrin and dry eye symptom score and rose bengal staining score. A negative association was also noted between tear IgA antibodies against alpha-fodrin and Schirmer I test. Conclusion. Correlation of IgG and IgA antibodies against alpha-fodrin with the seventy of eye involvement suggests that these autoantibodies may be considered activation markers of SS.
Keywords: Sjogren's syndrome; anti-alpha-fodrin antibodies; HYDROXYCHLOROQUINE TREATMENT; ANTIBODIES; MARKERS; IGA